Konsep Diri, Stres, dan Prokrastinasi Akademik pada Mahasiswa - Indah Handayani, Sri Wiworo Retno (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2012)
Abstract. The present research aims to find the correlation between self concept and stress with academic procrastination. The research sbjects were 337 students of faculty of psychology,Wisnuwardhana University. Data for this research were obtained by self concept scale, stress scale and academic procrastination scale. The data then were analyzed using SPSS for Windows 17, with regression analysis technique and then partial correlation. The results of regression analysis showed the significant correlation between self concept, stress and academic procrastination. The results of partial correlation analysis showed the negative correlation between self concept and procrastination, and other while, no correlation between stress and procrastination.Keywords : self concept, stress, procrastination